Assessing climate policies: an ecological stock–flow consistent perspective - Yannis Dafermos; Maria Nikolaidi (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
Addressing the climate crisis requires a deep socio-ecological transformation of our economies. This transformation involves the implementation of climate policies that not only transform standard macroeconomic and financial tools but also lead to sufficiency-based consumption patterns. The assessment and design of such policies require a systems-based approach that is not restricted by the straightjacket of cost–benefit analysis. In this paper, the authors employ an ecological stock–flow consistent model to provide a systems-based evaluation of certain macroeconomic, financial and sufficiency policies for climate mitigation. They show how the use of such an approach allows them to identify policy mixes that have the potential to address the climate crisis without undermining macrofinancial and social stability.
Keywords: 330; ecological stock–flow consistent modelling; green macroeconomic and financial policies; consumption patterns; climate changeE12; E44; E52; E62; Q54; Q57